Cariprazine for negative symptoms in early psychosis: a pilot study with a 6-month follow-up - Pappa, Sofia; Kalniunas, Arturas; Maret, Jose (Frontiers in Psychiatry, 2023)
Background Cariprazine, a novel antipsychotic drug that is a partial agonist with preferential binding to the D3 receptor, has demonstrated efficacy in clinical trials across all symptom domains, including negative symptoms, which can occur early in the course of psychotic illness. However, evidence, to date regarding its effects in early psychosis patients with primary negative symptoms has been limited. Objectives To evaluate the efficacy of cariprazine for negative symptoms in early psychosis patients. Methods Demographic and clinical information of the study population were collected from the electronic records and PANSS scale administered at baseline, 3 and 6 months. Tolerability and discontinuation reasons, where applicable, were also recorded. Results Ten patients with early psychosis (four men and six women, mean age – 25.5 years) with prominent or predominant negative symptoms were treated with cariprazine (range 1.5 – 3 mg). Three patients discontinued cariprazine within the first 3 months due to patient choice, lack of response and non-compliance, respectively. In the remaining patients, there was a significant reduction in the mean negative PANSS score from baseline to 6 months (from 26.3 to 10.6), mean total PANSS score (from 81.4 to 43.3) and in the mean positive PANSS score (from 14.4 to 9.9) which correspond to a 53.1, 41.5, and 28.5% mean score reduction. Conclusion This pilot study suggests that cariprazine is a safe and effective treatment in early psychosis, particularly for the alleviation of negative symptoms which remains an area of unmet treatment need.